Comparison of accuracy of hexed and nonhexed pickup impression copings in a multiple variable impression setup for recording multiple straight and angulated implant positions: An in vitro study - Tavleen Kaur; Shefali Singla; Lalit Kumar (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of this study was to evaluate and compare the accuracy of hexed and nonhexed pickup impression copings with and without splinting using polyether (PE) and polyvinyl siloxane (PVS) impression materials in open-tray technique in recording multiple straight and angulated implant positions. Settings and Design: An accurate impression results in an accurate definitive cast, thus minimizing the incidence of prosthesis misfit. The critical aspect is to record the three-dimensional location of the implant in bone rather than reproducing fine surface details. Precise fit of a fixed implant-supported prosthesis depends on the accuracy of the implant analog location within the definitive cast. Factors which affect impression accuracy include implant angulation, impression material, impression copings, technique, and splinting. Materials and Methods: A sample size of 80 study models fabricated from the impression of different groups was included. A reference master model based on All-on-4 implant concept with two parallel (implants 1 and 2) and two angulated (implant 3 at 17° and implant 4 at 30°) was fabricated using implant angulation guide. All impressions were recorded using open-tray impression technique. The groups were divided into two main groups of 40 samples each. Group A used hexed open-tray impression copings and Group B used nonhexed open-tray impression copings. Both the groups involved impression recording using splinted (Subgroup I) and nonsplinted impression copings (Subgroup II). Further, impressions in each subgroup were made using PE (Subsubgroups a) and PVS (Subsubgroup b). A total of eight subsubgroups with ten samples each were included. Impressions were recorded for each group and poured into Type IV die stone for fabrication of study models. After 24 h, the study models and reference master model were fitted with implant abutments for measurement with coordinate measuring machine. Statistical Analysis Used: The mean differences of the interimplant distance R1 (1-2), R2 (1-3), R3 (2-4), and R4 (3-4) between the reference model and sample models in different subsubgroups were calculated and three-way analysis of variance test was applied with Tukey's post hoc tests. Results: No significant difference was found in mean coronal deviations for distance R1, R2, and R3 (P > 0.05) between different study groups. P = 0.02 for R4 (distance between 17° and 30° implants) between impression materials subsubgroups suggested that significantly less distortion was created in location of highly angulated implants (>30°) using PVS impression material. Splinting and type of coping did not have a significant influence on impression accuracy. Increasing angulation decreased the accuracy. Conclusion: PVS was found equivalent in accuracy to rigid PE for recording parallel or angulated implants. Impressions of implants with higher angulations were recorded more accurately with PVS. The study found no difference in accuracy with or without splinting. Furthermore, nonhexed impression copings facilitate easier and accurate recording of multiple angulated implant location in bone.